Pengaruh Pendidikan, Pengangguran, dan Kemiskinan terhadap Ketimpangan Pendapatan di Indonesia - Hindun, Hindun; Soejoto, Ady; Hariyati, Hariyati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
This research aims to analyze the effect of education, unemployment, and poverty on income inequality in Indonesia, both partially and simultaneously. This research uses secondary data with a quantitative approach. The type of research used is the type of associative research. The variables in this study are education, unemployment, poverty, and income inequality "” data source from BPS and the Ministry of Education and Culture. The data analysis technique used is panel data regression analysis with cross-section 34 provinces and time series for 2015-2018. The results of the research obtained the random effect model, the best models. The results of data analysis show that education and poverty had a partial effect on income inequality in Indonesia, while unemployment had not to affect income inequality. Simultaneously, education, unemployment, and poverty affect income inequality in Indonesia. However, education, unemployment, and poverty can only explain 22.37% of the effect on income inequality in Indonesia. The rest is influenced by factors outside the model.